Correlative Fluorescence and Electron Microscopy in 3D—Scanning Electron Microscope Perspective. Issue 1 (3rd April 2017) - Franks, Jonathan; Wallace, Callen T.; Shibata, Masateru; Suga, Mitsuo; Erdman, Natasha; Stolz, Donna B.; Watkins, Simon C.
Abstract: The ability to correlate fluorescence microscopy (FM) and electron microscopy (EM) data obtained on biological (cell and tissue) specimens is essential to bridge the resolution gap between the data obtained by these different imaging techniques. In the past such correlations were limited to either EM navigation in two dimensions to the locations previously highlighted by fluorescence markers, or subsequent high‐resolution acquisition of tomographic information using a TEM. We present a novel approach whereby a sample previously investigated by FM is embedded and subjected to sequential mechanical polishing and backscatter imaging by scanning electron microscope. The resulting three dimensional EM tomogram of the sample can be directly correlated to the FM data. © 2017 by John Wiley & Sons, Inc.